A Wave Based approach for the dynamic bending analysis of Kirchhoff plates under distributed deterministic and random excitation. (August 2015) - Jonckheere, Stijn; Vandepitte, Dirk; Desmet, Wim
Highlights: The WBM for plate bending is extended with novel particular solutions. These particular solutions sets can account for a wide range of distributed loads. The method is validated on two deterministic cases with different load profiles. The WBM with the novel particular solutions outperforms conventional methods. The functions are successfully applied on random Turbulent Boundary Layer excitation. Abstract: For the harmonic analysis of plate bending problems, the Finite Element Method (FEM) is a commonly applied numerical technique. Its element concept with polynomial approximation functions, however, limits its applicable frequency range because of a strongly increasing computational cost. The Wave Based Method (WBM) has can relax this by using wave functions, which satisfy the governing differential equations. This paper derives two distinct particular solution sets for distributed loads in the WBM. Two numerical validations show the improved efficiency as compared to the FEM. The novel approach is also applied to a plate under a TBL excitation.